2017
DOI: 10.1002/elan.201700233
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Determination of Natural Drug Colchicine in Pharmaceuticals and Human Serum Sample and its Interaction with DNA

Abstract: Colchicine (COLC) is a natural toxic product and secondary metabolite most commonly used to treat gout. In this study, its electrochemical behavior and determination was investigated by employing modification‐free boron‐doped diamond electrode (BDDE). Besides, its interaction with DNA was monitored using electrochemical methods. It was found that oxidation of this compound proceeds in two steps, where first sharp and well defined oxidation peak occurs at potential of around 1.19 V, and second one at around 1.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Colchicine (COLC), a natural product used to treat gout, was quantified by Stankovic and coauthors using a DPV methodology . The authors used BR buffer at pH 7.5 on a bare BDD electrode.…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%
“…Colchicine (COLC), a natural product used to treat gout, was quantified by Stankovic and coauthors using a DPV methodology . The authors used BR buffer at pH 7.5 on a bare BDD electrode.…”
Section: Electroanalysis Of Pharmaceuticalsmentioning
confidence: 99%
“…Electrochemical methods, including voltammetry, are characterized by the high selectivity, sensitivity and a low cost of equipment. They are very often used for the determination of biologically active substances . To the best of our knowledge, no information about the analytical method for quantitative determination of IMT was described in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review revealed that numerous techniques have been applied for the analysis of probenecid in a single dosage form such as HPLC [4][5][6][7], TLC [8][9], spectrophotometric [10][11][12][13], capillary electrophoresis [14][15] and spectrofluremetriy [16]. Also, various techniques were reported for the single determination of colchicine as HPLC [17][18][19][20], TLC [21][22][23], spectrophotometry [24][25] and electrochemistry [26][27][28]. Only two chromatographic methods [29,30] has been reported for the determination of both drugs in binary mixture.…”
Section: Introductionmentioning
confidence: 99%